Evolving clonal nevus-case report with serial digital dermatoscopy and dermatopathology - Mike Inskip; Jill Magee (Mattioli1885, 2015)
We present a case of a clonal nevus arising from a previously banal melanocytic nevus over a 15-month period on the central back of a 30-year-old woman in a primary care skin cancer practice in Melbourne, Australia. Clinical, dermatoscopic and dermatopathologic images are presented. A search of the literature has discovered no previously published dermatoscopy images of an evolving clonal nevus.